(untitled) (Communication & Society, 2002)
Survey Research is a tool of scientific knowledge that exclusively works on the basis of statistical features. Classic scholars and numerous intellectuals frequently argue against this procedure because it seems to ignore the individual and to entirely focus on the masses. Still, the outcomes of opinion surveys cannot be understood as a negation of free will. The empirical verification of regularity in human conduct does not necessarily deny the existence of free will. It rather gives that free will its greatness as an ethical ideal.